THE SYSTEM OF PRECISION PLANNING MARINE SHIP’S VOYAGE - Sokolenko, Vasyliy (Proceedings of National Aviation University, 2016)
The paper considers the navigational path planning complex, which includes new original methods of developing a given algorithm of ship handling system operation and control over the process of moving on motion paths, including curved portions. We propose the algorithms of control over the process of movement and precision control methods in the management of the ship’s position. We created automatic place planning and control systems for curvilinear motion. The proposed concept gives a new direction to ensure the safe navigation of vessels in all driving conditions. This makes it possible to automate the process of planning and ship control when moving along the trajectories of arbitrary curvature. These benefits are achieved through: the development of high-precision methods of trajectory planning, which take into account the maneuvering characteristics of the vessel; improvement, using support systems control algorithms of decision-making in real-time; the use of automatic control of the center of gravity of the deviation from the set path precision methods; conversion of high-precision coordinate space satellite antenna on the determination of the vessel’s center of gravity; the use of high-precision calculation methods maneuvering characteristics; visualization process of movement and improving the efficiency of adjustment movement with a single remote control. The results can be used on ships to create a navigation device transition planning, as part of the pilot of the individual information devices and simulators for training navigators to control in cramped conditions.